Active Participation, Mind–Body Stabilization, and Coping Strategies with Integrative Medicine in Breast Cancer Patients - Theuser, Anna-Katharin; Antoniadis, Sophia; Langemann, Hanna; Wasner, Sonja; Grasruck, Katharina; Dietzel-Drentwett, Svenja; Fasching, Peter; Beckmann, Matthias; Hack, Carolin (Integrative Cancer Therapies, 2021)
Purpose: Increasing numbers of breast cancer survivors have led to a growing demand for integrative medicine. When patients have completed treatments associated with severe side effects, attention turns to reducing psychological symptoms, coping behavior, and self-care. The aim of this study was to assess patient-reported benefits in relation to active participation, mind–body stabilization, and coping strategies in breast cancer patients receiving integrative medicine. Methods: In a cross-sectional study, health counseling and treatment provided by a standardized integrative medicine consultancy service at the University Breast Center of Franconia were evaluated in 75 breast cancer patients over a 15-month period. At the baseline, the patients answered a questionnaire on their medical history, symptoms, and the treatment goals they were hoping to achieve with integrative medicine. Patient-reported outcomes relative to active participation, mind–body stabilization, and coping strategies were analyzed. Results: A large majority of the patients had previous experience with integrative medicine (91%). Most reported that they achieved their treatment goals with integrative medicine. Ninety-one percent achieved active participation in cancer treatment, 90% mind–body stabilization, and 79% improvement in coping strategies. Besides active participation, which was greatest in patients with stable disease, the success of integrative therapy was independent of age, concomitant diseases, previous integrative medicine experience, treatment state, and systemic cancer therapy. Conclusion: Breast cancer patients benefit from the counseling and treatment provided with integrative medicine in mind–body stabilization and coping with cancer. Active participation in cancer treatment is important for the patients. Integrative treatment services should form part of routine patient care.
CRIS-Team Scopus Importer:2021-03-19
Keywords: active participation; breast cancer; complementary and alternative medicine; coping; integrative medicine; mind–body; oncology

A Digital Home-Based Health Care Center for Remote Monitoring of Side Effects During Breast Cancer Therapy: Prospective, Single-Arm, Monocentric Feasibility Study - Hübner, Hanna; Wurmthaler, Lena; Goossens, Chloe; Ernst, Mathias; Mocker, Alexander; Krückel, Annika; Kallert, Maximilian; Geck, Jürgen; Limpert, Milena; Seitz, Katharina; Rübner, Matthias; Kreis, Philipp; et al. (JMIR Cancer, 2025)
Background: The introduction of oral anticancer therapies has, at least partially, shifted treatment from clinician-supervised hospital care to patient-managed home regimens. However, patients with breast cancer receiving oral cyclin-dependent kinase 4/6 inhibitor therapy still require regular hospital visits to monitor side effects. Telemonitoring has the potential to reduce hospital visits while maintaining quality care. Objective: This study aims to develop a digital home-based health care center (DHHC) for acquiring electrocardiograms (ECGs), white blood cell (WBC) counts, side effect photo documentation, and patient-reported quality of life (QoL) data. Methods: The DHHC was set up using an Apple Watch Series 6 (ECG measurements), a HemoCue WBC DIFF Analyzer (WBC counts), an iPhone SE (QoL assessments and photo documentation), a TP-Link M7350-4G Wi-Fi router, and a Raspberry Pi 4 Model B. A custom-built app stored and synchronized remotely collected data with the clinic. The feasibility and acceptance of the DHHC among patients with breast cancer undergoing cyclin-dependent kinase 4/6 inhibitor therapy were evaluated in a prospective, single-arm, monocentric study. Patients (n=76) monitored side effects—ECGs, WBC counts, photo documentation, and QoL—at 3 predefined time points: study inclusion (on-site), day 14 (remote), and day 28 (remote). After the study completion, patients completed a comprehensive questionnaire on user perception and feasibility. Adherence to scheduled visits, the success rate of the data transfer, user perception and feasibility, and the clinical relevance of remote measurements were evaluated. Results: Mean adherence to the planned remote visits was 63% on day 14 and 37% on day 28. ECG measurements were performed most frequently (day 14: 57/76, 75%; day 28: 31/76, 41%). The primary patient-reported reason for nonadherence was device malfunction. The expected versus the received data transfer per patient was as follows: ECGs: 3 versus 3.04 (SD 1.9); WBC counts: 3 versus 2.14 (SD 1.14); QoL questionnaires: 3 versus 2.5 (SD 1.14); and photo documentation: 6 versus 4.4 (SD 3.36). Among patients, 81% (55/68) found ECG measurements easy, 82% (55/67) found photo documentation easy, and 48% (33/69) found WBC measurements easy. Additionally, 61% (40/66) of patients felt comfortable with self-monitoring and 79% (54/68) were willing to integrate remote monitoring into their future cancer care. Therapy-induced decreased neutrophil count was successfully detected (P<.001; mean baseline: 4.3, SD 2.2, ×109/L; on-treatment: 1.8, SD 0.8, ×109/L). All-grade neutropenia and corrected QT interval prolongations were detected in 80% (55/68) and 2% (1/42) of patients, respectively. Conclusions: Adherence to scheduled remote visits was moderate, with nonadherence primarily attributed to device-related complications, which may have also affected the success rate of data transfer. Overall, patients considered remote monitoring useful and feasible. The prevalence of reported adverse events was comparable to existing literature, suggesting clinical potential. This initial feasibility study highlights the potential of the DHHC.
CRIS-Team Scopus Importer:2025-05-30
Keywords: breast cancer; CDK4/6 inhibitor; cyclin-dependent kinase 4/6 inhibitor; digital medicine; mobile phone; remote monitoring; telehealth

CDK4/6 Inhibition – Therapy Sequences and the Quest to Find the Best Biomarkers – an Overview of Current Programs - Schneeweiss, Andreas; Brucker, Sara Y.; Hübner, Hanna; Volmer, Lea L.; Hack, Carolin; Seitz, Katharina; Rübner, Matthias; Heublein, Sabine; Thewes, Verena; Lüftner, Diana; Lux, Michael P.; Jurhasz-Böss, Ingolf; et al. (Geburtshilfe und Frauenheilkunde, 2024)
In recent years, new targeted therapies have been developed to treat patients with hormone receptor-positive (HR+)/human epidermal growth factor receptor 2-negative (HER2-) breast cancer. Some of these therapies have not just become the new therapy standard but also led to significantly longer overall survival rates. The cyclin-dependent kinase 4 and 6 inhibitors (CDK4/6i) have become the therapeutic standard for first-line therapy. Around 70 - 80% of patients are treated with a CDK4/6i. In recent years, a number of biomarkers associated with progression, clonal selection or evolution have been reported for CDK4/6i and their endocrine combination partners. Understanding the mechanisms behind treatment efficacy and resistance is important. A better understanding could contribute to planning the most effective therapeutic sequences and utilizing basic molecular information to overcome endocrine resistance. One study with large numbers of patients which aims to elucidate these mechanisms is the Comprehensive Analysis of sPatial, TempORal and molecular patterns of ribociclib efficacy and resistance in advanced Breast Cancer patients (CAPTOR BC) trial. This overview summarizes the latest clinical research on resistance to endocrine therapies, focusing on CDK4/6 inhibitors and discussing current study concepts.
CRIS-Team Scopus Importer:2024-06-14
Keywords: breast cancer; CDK4/6; therapy

Current landscape of hospital information systems in gynecology and obstetrics in Germany: a survey of the commission Digital Medicine of the German Society for Gynecology and Obstetrics - Pfob, André; Griewing, Sebastian; Seitz, Katharina; Hillen, Christoph; Becker, Sven; Bayer, Christian; Wagner, Uwe; Fasching, Peter; Wallwiener, Markus; Abele, Harald; Alexa, Matthias; Cieslik, Jan Philipp; et al. (Archives of Gynecology and Obstetrics, 2023)
Purpose: Hospital information systems (HIS) play a critical role in modern healthcare by facilitating the management and delivery of patient care services. We aimed to evaluate the current landscape of HIS in the specialty of gynecology and obstetrics in Germany. Methods: An anonymous questionnaire was distributed via the German Society of Gynecology and Obstetrics newsletter in December 2022. The questionnaire covered the domains baseline demographic information, satisfaction with daily use, satisfaction with implementation, and degree of digitization. Results: Ninety-one participants completed the survey. Median age was 34 years; 67.4% (60 of 89) were female, and 32.6% (29 of 89) were male. Of the survey participants, 47.7% (42 of 88) were residents, 26.1% (23 of 91) senior physicians, and 9.1% (8 of 88) medical directors. The degree of digitization of clinical documentation is mainly mixed digital and paper-based (64.0%, 57 of 89) while 16.9% (15 of 89) operate mainly paper-based. The current HIS has been in use on average for 9 years. The median number of different software systems used in daily routine is 4. About 33.7% (30 of 89) would likely or very likely recommend their current HIS to a colleague. Conclusions: The current landscape of HIS in gynecology and obstetrics in Germany is characterized by a high heterogeneity of systems with low interoperability and long service life; thus, many healthcare professionals are not satisfied. There is both a need to enhance and an interest in modernizing the technological infrastructure to meet today’s requirements for patient care.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Artificial intelligence; Digital health; eHealth; Gynecology and obstetrics; Implementation

Evaluation of automated techniques for extraction of circulating cell-free DNA for implementation in standardized high-throughput workflows - Lehle, Sarah; Emons, Julius; Hack, Carolin; Heindl, Felix; Hein, Alexander; Preuß, Caroline; Seitz, Katharina; Zahn, Anna; Beckmann, Matthias; Fasching, Peter; Rübner, Matthias; Hübner, Hanna (Scientific Reports, 2023)
Analysis of circulating cell-free DNA (ccfDNA) is a suitable tool for detecting somatic mutations for the purpose of making decisions on treatment, monitoring treatment response, and predicting survival. High-throughput techniques for ccfDNA extraction are essential to implementing ccfDNA testing in the clinical setting. We set out to compare two automated techniques with regard to hands-on time, ccfDNA output and integrity, and circulating mitochondrial DNA (mtDNA). CcfDNA was isolated using the EZ1&2 ccfDNA field test kit (EZ2 kit, QIAGEN) and the Maxwell RSC ccfDNA plasma kit (Maxwell kit, Promega). DNA was extracted from plasma of 30 breast cancer patients enrolled in the iMODE-B (#325_19B; 12.10.2020) study. Real-time PCR, fluorescence-based detection and automated electrophoresis were used to assess ccfDNA concentrations. The ccfDNA yield was significantly higher when extracted with the EZ2 kit. The EZ2 kit enabled the isolation of a higher proportion of short fragments and a lower proportion of long fragments, resulting in lower DNA integrity. Significantly lower mtDNA quantities were detected in the Maxwell eluate than in the EZ2 eluate. Thus, decisions on which extraction method to use should proceed on the basis of the required input for downstream applications, the anticipated fragment size and minimum hands-on time.
CRIS-Team Scopus Importer:2023-01-20

Methodological Establishment of an in-vitro ADCC Assay by using patient-specific Immune Cells - Lehle, Sarah; Völkl, Simon; Rübner, Matthias; Emons, Julius; Seitz, Katharina; Beckmann, Matthias; Fasching, Peter; Hübner, Hanna (GEBURTSHILFE UND FRAUENHEILKUNDE, 2022)
CRIS-Team WoS Importer:2022-11-04

Patterns and Trends of Herbal Medicine Use among Patients with Gynecologic Cancer - Theuser, Anna Katharin; Hack, Carolin; Fasching, Peter; Antoniadis, Sophia; Grasruck, Katharina; Wasner, Sonja; Knoll, Stefanie; Sievers, Hartwig; Beckmann, Matthias; Thiel, Falk C. (Geburtshilfe und Frauenheilkunde, 2021)
Background More and more information about complementary and integrative medicine is becoming available, especially among cancer patients. However, little is known about the use of herbal medicine by patients with gynecologic cancers. This study aimed to assess the use of herbal products by gynecologic cancer patients compared with healthy controls. Methods This cross-sectional study was conducted at the Department for Gynecology and Obstetrics of Erlangen University Hospital and included 201 patients with gynecologic cancer and 212 healthy controls. Use of herbal medicines was evaluated using a standardized questionnaire. Medical information on cancer patients was collected from hospital records. Group comparisons were done using a logistic regression model. Risk ratios were assessed using a Poisson regression model. Results Gynecologic cancer patients used herbal medicine significantly less often than healthy persons. 69% of gynecologic cancer patients and 81% of healthy participants reported using herbal products. 40% of cancer patients and 56% of healthy persons reported using plants for medicinal purposes. Motives of cancer patients for using herbal medicine included treatment of cancer-related symptoms. The major source of information for both groups was family and friends. Conclusions Although herbal medicine was used less by patients with gynecologic cancer, herbal products were used by both cancer patients and healthy individuals. To provide cancer patients with optimal therapy, oncologists should be informed about the herbal products used by their patients as this will allow them to take their patients' self-medication with herbal medicine into account. Counseling by oncologists on the use of herbal medicine should be encouraged.
CRIS-Team Scopus Importer:2021-07-02
Keywords: cancer; complementary and alternative medicine; gynecologic oncology; herbal medicine; integrative medicine

Perspectives of patients and clinicians on big data and AI in health: a comparative empirical investigation - Hummel, Patrik; Braun, Matthias; Bischoff, Serena; Samhammer, David; Seitz, Katharina; Fasching, Peter; Dabrock, Peter (AI and Society, 2024)
Background: Big data and AI applications now play a major role in many health contexts. Much research has already been conducted on ethical and social challenges associated with these technologies. Likewise, there are already some studies that investigate empirically which values and attitudes play a role in connection with their design and implementation. What is still in its infancy, however, is the comparative investigation of the perspectives of different stakeholders. Methods: To explore this issue in a multi-faceted manner, we conducted semi-structured interviews as well as focus group discussions with patients and clinicians. These empirical methods were used to gather interviewee’s views on the opportunities and challenges of medical AI and other data-intensive applications. Results: Different clinician and patient groups are exposed to medical AI to differing degrees. Interviewees expect and demand that the purposes of data processing accord with patient preferences, and that data are put to effective use to generate social value. One central result is the shared tendency of clinicians and patients to maintain individualistic ascriptions of responsibility for clinical outcomes. Conclusions: Medical AI and the proliferation of data with import for health-related inferences shape and partially reconfigure stakeholder expectations of how these technologies relate to the decision-making of human agents. Intuitions about individual responsibility for clinical outcomes could eventually be disrupted by the increasing sophistication of data-intensive and AI-driven clinical tools. Besides individual responsibility, systemic governance will be key to promote alignment with stakeholder expectations in AI-driven and data-intensive health settings.
CRIS-Team Scopus Importer:2024-01-12
Keywords: Big data; Ethics; Health; Interviews; Privacy; Self-determination; Stakeholder

Prognosis prediction with the IHC3 score in patients with node-negative, hormone receptor-positive, HER2-negative early breast cancer - Seitz, Katharina; Goossens, Chloe; Hübner, Hannah; Gaß, Paul; Uhrig, Sabrina; Heindl, Felix; Emons, Julius; Rübner, Matthias; Anetsberger, Daniel; Hartmann, Arndt; Beckmann, Matthias; Erber, Ramona; et al. (ESMO Open, 2024)
Background: Prognostication has been used to identify patient populations that could potentially benefit from treatment de-escalation. In patients with hormone receptor-positive (HRpos), human epidermal growth factor receptor 2-negative (HER2neg) early breast cancer (eBC), treatment de-escalation classically involved omitting chemotherapy. With recently developed specialized therapies that require hands-on side-effect management, the therapeutic landscape is changing and therapy decisions are no longer based only on prognosis, but also consider potential side-effects. Therefore, identification of patient groups based on prognostication has gained importance. Materials and methods: In this retrospective analysis, a population of 2359 node-negative HRpos/HER2neg eBC patients was selected from all patients treated at the University Breast Center of Franconia, Germany between 2002 and 2021. The prognostic value of the IHC3 score (incorporating immunohistochemical measurements of the estrogen and progesterone receptor status and Ki-67) with clinical parameters (lymph node status, tumor stage, grading) regarding invasive disease-free survival (iDFS) and overall survival (OS) was assessed. Results: IHC3 positively correlated with Ki-67 expression and inversely correlated with hormone receptor expression. IHC3 categorized into quartiles identified patients with a more unfavorable prognosis: 5-year and 10-year iDFS rates for patients in the highest versus the lowest quartile were 84% versus 95% and 70% versus 88%, respectively. A sensitivity analysis of distant disease-free survival showed similar results to those of iDFS. Five-year and 10-year OS rates for patients in the highest versus the lowest quartile were, respectively, 92% versus 97% and 81% versus 92%. Conclusions: IHC3 is able to define prognostic groups in patients with node-negative, HRpos/HER2neg eBC. Node-negative patients with a high IHC3 score had the worst prognosis, which was comparable to that of node-positive patients described in recent trials. This simple and cost-effective tool could thus potentially aid in identifying patient groups for innovative therapeutic approaches.
CRIS-Team Scopus Importer:2024-11-01
Keywords: early breast cancer; hormone receptor-positive; IHC3; molecular marker; prognosis

Status quo and future directions of digitalization in gynecology and obstetrics in Germany: a survey of the commission Digital Medicine of the German Society for Gynecology and Obstetrics - Pfob, André; Hillen, Christoph; Seitz, Katharina; Griewing, Sebastian; Becker, Sven; Bayer, Christian; Wagner, Uwe; Fasching, Peter; Wallwiener, Markus (Archives of Gynecology and Obstetrics, 2024)
Purpose: Digitalization plays a critical role and is beginning to impact every part of the patient journey, from drug discovery and data collection to treatment and patient-reported outcomes. We aimed to evaluate the status quo and future directions of digital medicine in the specialty of gynecology and obstetrics in Germany. Methods: An anonymous questionnaire was distributed via the German Society of Gynecology and Obstetrics newsletter in December 2022. The questionnaire covered the domains baseline demographic information, telemedicine, digital health applications (DIGAs), and future expectations. Results: In all, 91 participants completed the survey. Median age was 34 years; 67.4% (60 of 89) were female and 32.6% (29 of 89) were male. About 10% (9 of 88) have prescribed DIGAs to date and 14% (12 of 86) offer telemedical appointments. Among those who do not use digital medicine, very few plan to do so in the near future. Reasons include missing software interfaces, lack of time to try out new things, lack of knowledge, lack of monetary compensation (66.3%), and employee concerns. A majority agreed that digitalization will help to save time and improve patient care and that intelligent algorithms will aid clinicians in providing patient care to women. Conclusions: The status quo and future directions of digital medicine in gynecology and obstetrics in Germany are characterized by contradicting expectations regarding the benefits of digital medicine and its actual implementation in clinical routine. This represents an important call to action to meet the requirements of modern patient care.
CRIS-Team Scopus Importer:2023-12-08
Keywords: Artificial intelligence; Digital health; eHealth; Gynecology and obstetrics; Implementation

Update Breast Cancer 2022 Part 1 - Early Stage Breast Cancer. - Welslau, Manfred; Mueller, Volkmar; Lueftner, Diana; Schuetz, Florian; Stickeler, Elmar; Fasching, Peter; Janni, Wolfgang; Thomssen, Christoph; Witzel, Isabell; Fehm, Tanja N.; Belleville, Erik; Bader, Simon; et al. (Geburtshilfe und Frauenheilkunde, 2022)
Evidence relating to the treatment of breast cancer patients with early-stage disease has increased significantly in the past year. Abemaciclib, olaparib, and pembrolizumab are new drugs with good efficacy in the relevant patient groups. However, some questions remain unanswered. In particular, it remains unclear which premenopausal patients with hormone receptor-positive breast cancer should be spared unnecessary treatment. The question of the degree to which chemotherapy exerts a direct cytotoxic effect on the tumor or reduces ovarian function through chemotherapy could be of key importance. This group of patients could potentially be spared chemotherapy. New, previously experimental biomarker analysis methods, such as spatial analysis of gene expression (spatial transcriptomics) are gradually finding their way into large randomized phase III trials, such as the NeoTRIP trial. This in turn leads to a better understanding of the predictive factors of new therapies, for example immunotherapy. This review summarizes the scientific innovations from recent congresses such as the San Antonio Breast Cancer Symposium 2021 but also from recent publications.
EVALuna2:511215

Update Breast Cancer 2022 Part 2 - Advanced Stage Breast Cancer - Müller, Volkmar; Welslau, Manfred; Lüftner, Diana; Schütz, Florian; Stickeler, Elmar; Fasching, Peter; Janni, Wolfgang; Thomssen, Christoph; Witzel, Isabell; Fehm, Tanja N.; Belleville, Erik; Bader, Simon; et al. (Geburtshilfe und Frauenheilkunde, 2022)
For patients with advanced breast cancer, several novel therapies have emerged in recent years, including CDK4/6 inhibitors, immune checkpoint inhibitors, PARP inhibitors, alpelisib, tucatinib and trastuzumab-deruxtecan, and sacituzumab-govitecan, which have transformed and expanded the therapeutic landscape for patients with advanced breast cancer. Some of these substances have now been approved for use in the early stages of the disease, or are expected to be approved in the near future, so the therapeutic landscape will change once again. Therefore, current scientific efforts are focused on the introduction of new substances and understanding their mechanisms of progression and efficacy. This review summarizes recent developments with reference to recent publications and conferences. Findings on the treatment of patients with HER2-positive breast cancer and brain metastases are presented, as are a number of studies looking at biomarkers in patients with HER2-negative, hormone receptor-positive breast cancer. In particular, the introduction of oral selective estrogen receptor degraders provides new opportunities to establish biomarker-based therapy. Molecular diagnostics is establishing itself as a diagnostic marker and parameter of progression.
CRIS-Team Scopus Importer:2022-08-05
Keywords: ADC; biomarker; breast cancer; metastatic; PD-L1